Coaching for sports performance - Baghurst, Timothy M. 1979-
"Coaching for Sports Performance provides a practical overview of the many disciplines necessary to be an effective coach. Using experts from across the sports science fields, this book teaches readers the core concepts in a practical, easy to understand style, separated into four sections. Part I explains the fundamentals of effective coaching including the development of coaching philosophies, best practices for coaching effectively, how athletic technique matures, and what coaches can and cannot do in specific health-related situations. Part II provides practical ways to improve athletic performance where readers learn the fundamentals of biomechanics and how to use technology to analyze performance, the physiological functions and adaptations to exercise, how the body can be physically trained and properly fueled, and mental strategies to optimize athletic outcomes. Part III introduces the business side of coaching, the important responsibilities involved in sport management, and practical methods for marketing as well as working with the media. Last, Part IV offers specific strategies for coaching across age and skill levels. Chapters are split into youth and high school, collegiate, and professional athletes, and the nuances of coaching each level are explained. Being called "Coach" is an honor, but with this title comes the responsibility of being professional, knowledgeable, and effective. Coaching for Sports Performance provides the platform for becoming a successful coach and assisting athletes in achieving their potential. Coaching for Sports Performance provides a practical overview of the many disciplines necessary to be an effective coach"--Provided by publisher.